2013
DOI: 10.15823/p.2013.1844
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education Teacher’s Opinion about Learners’ Personal Qualities as a Precondition of Pedagogical Interaction

Abstract: The article deals with the personal qualities of the tenth grade pupils which are perceived as the disturbances and the stimulus of educational interaction by physical education teachers in physical education classes. Research results have shown that all physical education teachers participating in the study (both men and women) are positive about three personal qualities of pupils: curiosity, self-confidence and initiative. According to the respondents, those qualities mentioned above help develop pedag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Notably, more than one-third of the teachers had negative attitudes toward social communication in general. This finding is in line with the observations of Kardeliene and Kardelis (2006), who found that the linguistic behaviour of some physical education teachers was dominated by a hierarchical approach to communication. Specifically, the authors mentioned the teachers' occasional use of unsuitable expressions during physical education lessons, especially when the learner failed in some exercise.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, more than one-third of the teachers had negative attitudes toward social communication in general. This finding is in line with the observations of Kardeliene and Kardelis (2006), who found that the linguistic behaviour of some physical education teachers was dominated by a hierarchical approach to communication. Specifically, the authors mentioned the teachers' occasional use of unsuitable expressions during physical education lessons, especially when the learner failed in some exercise.…”
Section: Discussionsupporting
confidence: 92%
“…An analysis of teachers' work environment characteristics highlighted educators' social communication as a critical element (Mazer et al, 2014). Some scholars have reported that the social communication attitudes of physical education teachers are dominated by conservativism (Kardeliene, Kardelis, 2006;Masiliauskas, 2011). Arguably, physical education teachers at schools are more likely to focus on the teaching subject than the personality of the learner.…”
Section: Literature Reviewmentioning
confidence: 99%